Hubungan Komitmen Organisasi dan Beban Kerja dengan Kinerja Perawat di RSUD Kembangan Tahun 2024 - Indah Septiani; Solehudin Solehudin; Saiful Gunardi (Calory Journal Medical Laboratory Journal, 2024)
Performance is the result of work in terms of quality and quantity achieved by an employee in carrying out his duties in accordance with the responsibilities given to him. This study aims to identify the Relationship Between Organizational Commitment and Workload with Nurse Performance at Kembangan Hospital in 2024. The research method used is correlation analysis with a cross-sectional design approach. The sample of this study consisted of 88 nurses working at Kembangan Hospital, the technique used was total sampling. Data were collected through a questionnaire that measured the level of organizational commitment, workload, and nurse performance. The results showed that organizational commitment had a positive and significant effect on nurse performance (p <0.05). This means that the higher the organizational commitment of the nurse, the better the performance shown. Conversely, workload has a negative and significant effect on nurse performance (p <0.05). This shows that high workload tends to reduce nurse performance. Conclusion: The results of the study show a Relationship Between Organizational Commitment and Workload with Nurse Performance at Kembangan Hospital in 2024.